2007
DOI: 10.1002/bsl.742
|View full text |Cite
|
Sign up to set email alerts
|

An examination of behavioral consistency using individual behaviors or groups of behaviors in serial homicide

Abstract: Establishing behavioral consistency in serial homicide offending behavior is essential when linking homicides together and to a common offender. An examination of 35 serial homicide behaviors utilized by 90 offenders in 450 serial homicide cases was carried out to identify whether these offenders consistently performed the same behaviors across their series of homicides and whether it is more effective to examine individual behaviors or groupings of behaviors in order to identify behavioral consistency. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 16 publications
3
74
0
1
Order By: Relevance
“…Behaviours that are cognitively mediated are hypothesised to show less cross-situational consistency because the demands made by the situation become less important (Shoda, Mischel, & Wright, 1993). If victim resistance was considered a situational feature that might cause an offender negative affect or stress, this might partly explain why greater consistency has been observed in control behaviours in serial stranger sex offences, homicide, and robbery (Bateman & Salfati, 2007;Grubin, Kelly, & Brunsdon, 2001;Woodhams & Toye, 2007;. Evidence from personality psychology for the mediation effect of automatic versus cognitively mediated behaviours is, however, mixed (Furr & Funder, 2004).…”
Section: Situational Similarity As Partner Typementioning
confidence: 96%
See 1 more Smart Citation
“…Behaviours that are cognitively mediated are hypothesised to show less cross-situational consistency because the demands made by the situation become less important (Shoda, Mischel, & Wright, 1993). If victim resistance was considered a situational feature that might cause an offender negative affect or stress, this might partly explain why greater consistency has been observed in control behaviours in serial stranger sex offences, homicide, and robbery (Bateman & Salfati, 2007;Grubin, Kelly, & Brunsdon, 2001;Woodhams & Toye, 2007;. Evidence from personality psychology for the mediation effect of automatic versus cognitively mediated behaviours is, however, mixed (Furr & Funder, 2004).…”
Section: Situational Similarity As Partner Typementioning
confidence: 96%
“…Behavioural consistency in control behaviours has now been investigated for serial robbery, rape, and homicide (e.g. Bateman & Salfati, 2007;Grubin, Kelly, & Brunsdon, 2001;Woodhams & Toye, 2007), and thus control appears to be one domain that is shared by more than one offence type. Such an analysis was beyond the scope of the current paper due to the available data set, but this research question would benefi t from exploration in the future.…”
Section: Rationalementioning
confidence: 98%
“…behavioural consistency). Recent empirical studies (Bateman & Salfati, 2007;Salfati & Bateman, 2005) have found little evidence of consistency looking at either individual, group or themes of behaviours in serial homicide. Several factors have been proffered to explain the inconsistencies in offenders' behaviours, such as maturation, development, and learning (Canter & Youngs, 2003;Salfati, 2008).…”
mentioning
confidence: 98%
“…Although several studies successfully identifi ed evidence of consistency across series of sexual crimes for linkage purposes (Bateman & Salfati, 2007;Canter, Heritage, Wilson, Davies, Kirby, Holden, McGinley, Hughes, Larkin, Martin, Tsang, Vaughan, & Donald, 1991;Grubin, Kelly, & Brunsdon, 2001;Salfati & Bateman, 2005;Santtila, Junkkila, & Sandnabba, 2005;Woodhams, Grant, & Price, 2007a), Woodhams, Hollin, and Bull (2008) found little support for consistency in cases of serial sexual assaults using if-then contingencies. Interestingly, fi ndings from sex offender and profi ling research point towards the same direction, suggesting that these offenders display both consistency and versatility depending on the situation, as well as the specifi c actions, observed.…”
Section: 'Crime-switching' Patterns In Sex Offendersmentioning
confidence: 97%